Suberin in plants: biosynthesis, regulation, and its role in salt stress resistance - Chen, Ruonan; Wang, Pengrui; Liu, Jianing; Yang, Xue; Gong, Xiaoying; Zhou, Hongliang; Han, Ning; Yang, Zhen (Frontiers in Plant Science, 2025)
Soil salinization represents a significant global ecological challenge. Plants encounter salt stress in their growth environments. Suberin, a hydrophobic polymer, plays a critical role in plant salt tolerance. This review examines the mechanisms by which suberin contributes to salt tolerance. Suberin comprises polyaliphatic and polyphenolic domains. Its biosynthesis involves multiple enzymes, including fatty acid synthases, the fatty acid elongation complex, and various cytochrome P450 monooxygenases. ABCG transporters and lipid transfer proteins facilitate the transport of suberin monomers from the endoplasmic reticulum to the plasma membrane and cell wall. Plants utilize suberin lamellae to respond to salt stress through multiple mechanisms. Under salt stress, the structure and composition of suberin lamellae undergo modifications, including increased thickness and enhanced very-long-chain fatty acid components. In addition, salt stress elevates the expression of genes associated with suberin biosynthesis and transport. Mutations in these genes often result in salt-sensitive phenotypes. Fundamentally, suberin contributes to forming the hydrophobic component of the apoplastic barrier, thereby reducing passive Na+ influx and restricting sodium uptake to protect plants from ion toxicity. Understanding the mechanisms of suberin in salt tolerance offers potential strategies for enhancing crop salt tolerance through genetic engineering.